Design of a joint radar and communication system - Saseedaran, Shiju (Nanyang Technological University, 2019)
In recent years, personal mobility devices (PMD) have become increasingly popular as they provide a convenient form of transportation for users. However, there have been concerns over the safe usage of these devices. Although regulations have been enforced to ensure safety, no system has been implemented on PMDs to reduce human errors that may occur when riding. In this project, a design of a joint radar and communication system for PMDs would be proposed to increase the situational awareness in users. This would reduce human errors when riding thus enforcing safety. A frequency modulated continuous wave (FMCW) radar, similar to radars used in automotive applications, would first be designed and tested for its range detection capabilities. From there, binary phase-shift keying (BPSK) modulation scheme would be implemented onto the radar signal to form a joint radar and communication system. With the inclusion of the modulation scheme, tests would be carried out to attain the optimal modulation parameters that would allow ideal radar performance in the joint system. The performance of the communication component of the joint system would also be evaluated with these parameters. Information would then be sent through the communication link to observe whether successive information transfer can be achieved by the joint system. Through the execution of all of the experiments, the efficiency of the simultaneous operation of both the radar and communication components of the joint system would be verified.